Characterization of three fowl adenovirus isolates of Malaysia propagated in chicken embryo liver cells - Ugwu, Chidozie Clifford; Bejo, Mohd Hair; Mat Isa, Nurulfiza; Omar, Abdul Rahman; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The objectives of this study were to characterize fowl adenovirus (FAdV) isolates of Malaysia propagated in chicken embryo liver (CEL) cells. Three isolates of FAdV namely; UPM11142, UPM11134 and UPM08136 were used. They were first propagated in specific pathogen free (SPF) chicken embryonated eggs (CEE) once (E1) and further propagated in CEL cells for 5 consecutive passages (CELP1 to CELP5). The E1, CELP1 and CELP5 of all of the isolates were characterized by PCR technique. The PCR products were then sequenced and analyzed. The study showed that all the isolates caused mortality in SPF CEE eggs and adapted well in CEL cells. Eosinophilic intranuclear inclusion bodies were observed in the cells. The UPM11142 and UPM11134 exhibited more pathogenic in CEE and CEL cells than UPM08136. All of the FADV isolates were characterized as FAdV group E serotype 8b. Nucleotide and amino acid changes were recorded in CELP1 and CELP5 when compared to E1. These isolates have potential to be used for vaccine development against the disease.